Percepção e conhecimento dos profissionais de saúde que atuam nas unidades neonatais com relação ao manejo da dor no recém-nascido - Martins, Renata Souza (2010)
The Neonatal Intensive Care Units (NICU) are places where several painful procedures are performed in the newborns. They express the painful sensation through behavioral and physiological changes. The measures to evaluate, prevent and treat the newborn pain have not yet been used in a systematic way by the health professionals who provide care to the newborn infants admitted. So, the purpose of this project was to evaluate how the pediatricians and other doctors, nurses and physical therapists who work on Neonatal Units, understand the issue of pain and its management. This was an observational study, accomplished through a cross-sectional field survey, with the analysis of data collected through questionnaires with professionals who worked in neonatal units. One hundred and thirty-seven (137) professionals were supposed to be interviewed. They were 24 nurses, 11 physical therapists, 63 pediatricians and 39 doctors from different areas. One hundred and twenty (120) professionals have been interviewed, among them 22 nurses (91,6%), 11 physical therapists (100%), 56 pediatricians (88,8%) and 31 doctors from different areas (79,5%). Among the results, 100% of the interviewed professionals believed that the newborn feels pain. The majority of nurses, physical therapists and pediatricians claimed to know some pain scales assessment, and mostly referred to facial mime as an evaluation parameter. It was observed that pediatricians were more aware of these pain scales assessments than the doctors from other areas. The majority of the interviewed professionals reported the use of measures to prevent and treat the pain in the neonate. The nurses and physical therapists preferred nonpharmacological measures; the doctors mostly reported the use of pharmacological measures and fentanyl was the most used medication. In relation to the accomplishment of measures to treat the pain during the potentially painful procedures, the nurses claimed to use nonpharmacological measures to ease the pain or to request a prescription of medication in most of the procedures, while the minority of pediatricians attributed treatment in procedures like venipuncture (46,4%), heel puncture (33,9%) and lumbar puncture (41,1%). The majority of pediatricians reported the use of pharmacological measures in newborns that had been under mechanical ventilation (96,4%), undergone venous dissection (89,3%), thoracic drainage (92,9%), and in the post-operative of neonate in need of mechanical ventilation (98,2%) or not (98,2%). With these results it is conclusive that the health professionals are aware of the management of the neonate pain. However it is necessary to implement routines and protocols in the neonatal services, as well as training to professionals who work in these units, making sure that the knowledge related to prevention, evaluation and treatment of the pain on the neonatal period will be used.